Developing the Integrated Control Systems Media for Enhancing the Electrification Competency of Electric Railway Drive - Rizqi Ervani (Elinvo (Electronics, Informatics, and Vocational Education), 2025)
This study aimed to determine the operation of the integrated control media for the traction system in electric railway drives at the Polytechnic, to assess the feasibility of the integrated control media for the traction system, and to produce an effective integrated control media for the traction system that can be used to increase the electrification competence of electric railway drives. This study was conducted using a development research approach, employing the RAD (Rapid Application Development) and ASSURE methods. The subjects of this study were 39 students from the Madiun State Polytechnic Railway. Data was collected using observation sheets, interview sheets, media questionnaires, module questionnaires, and tests. Validation of the questionnaire instrument was carried out using Aiken's-V formula and Pearson Product-Moment correlation, while the reliability test of the test instrument used Cronbach's Alpha. The validity coefficient of the material and media questionnaire instrument falls into the category of "Feasible". The data was analyzed in combination, where the qualitative data were carried out using Huberman's steps, and the quantitative data were descriptive, the Wilcoxon test, and the Gain Score value. The results of this study can be stated that the operation of the integrated control media for the traction system in electric train (EMU) drivers at the Polytechnic is "Very Feasible", the feasibility of the integrated control media for the traction system is "Very Feasible" with a significance of 0.00. The final results are applications and teaching modules for traction systems used as learning support during the railway electrical engine practicum at the Madiun State Polytechnic Railway.